Usefulness of molecular diagnosis in egg allergic children - Petrosino, Marianna I. (Arch Med Sci, 2016)
INTRODUCTION: Egg allergy is one of the most common food allergies in children. Egg white, including ovomucoid (OVM or Gal d 1) and ovalbumin (OVA or Gal d 2), is the major source of allergens. The aim of this study was to assess the role of Gal d 1 and Gal d 2 in predicting the risk of anaphylaxis caused by eggs in children, and to compare this new diagnostic tool with established methods of allergen-specific IgE detection. MATERIAL AND METHODS: One hundred and forty-eight children were divided into 2 groups according to a positive (group A, 33 children) or negative (group B, 115 children) history of anaphylaxis after ingestion/contact with eggs. All patients underwent an allergological evaluation by measurements of specific IgE against egg white: Gal d 1 and Gal d 2. RESULTS: Higher levels of Gal d 1, Gal d 2 and IgE against egg white were detected in group A compared to group B (p < 0.001). Although the area under the curve was similar for Gal d 1 and Gal d 2, egg white specific IgE showed a better sensitivity (85%) for a cut-off value ≥ 0.975 kUA/l, while Gal d 1 and Gal d 2 demonstrated a better specificity (90% and 80%, respectively) for cut-off values ≥ 1.460 kUA/l and ≥ 2.310 kUA/l, respectively. CONCLUSIONS: Egg white specific IgE showed a similar ability as Gal d 1 and Gal d 2 in differentiating children at risk for egg anaphylaxis, although Gal d 1 and Gal d 2 showed a better specificity.